Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (Tsts) Terhadap Kemampuan Pemahaman Konsep Matematis Peserta Didik Kelas VIII SMPN 2 Pariaman Tahun Pelajaran 2018/2019 - EFRINA RIZKI (Jurnal Edukasi dan Penelitian Matematika, 2019)
The ability of understanding mathematical concepts has a very important role needed in an effort to achieve the goals of mathematics learning. The ability to understand the concept should be developed through the learning process. However, mathematics learning that occurred in class VIII of SMP 2 Pariaman has not yet involved students optimally in the process of rediscovering the concept so that the ability of understanding mathematical concepts of students has not been well developed. In addition, the participation or active role of students in learning also seems to be lacking. This has an impact on the low ability to understand  the mathematical concepts of students. An alternative that can be used as a solution to overcome the above problems is learning using the cooperative learning model type TSTS. This type of research is a quasi-experimental design with Static Group Design. The research hypothesis is carried out using the t-test. Based on the results of data analysis, it was concluded that the ability of understand mathematical concepts of students who learn with the cooperative learning model type TSTS is better than ability of understand mathematical concepts of students who learn with conventional learning.